The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1557/jmr.2013.261
|View full text |Cite
|
Sign up to set email alerts
|

Properties of epitaxial graphene grown on C-face SiC compared to Si-face

Abstract: Epitaxial graphene of uniform thickness prepared on SiC is of great interest for various applications. On the Si-face, large area uniformity has been achieved, and there is a general consensus about the graphene properties. A similar uniformity has yet not been demonstrated on the C-face where the graphene has been claimed to be fundamentally different. A rotational disorder between adjacent graphene layers has been reported and suggested to explain why multilayer C-face graphene show the p-band characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…At present, there exist several interpretations about the rotational disorder on this system. Several groups reported that the disorder is due to the rotation between graphene layers inside one single domain [14,15], the Bernal stacked azimuthally disordered graphene domains [12,[22][23][24], or a combination of AB stacked and twisted multilayers [26]. We now present our results obtained from graphene with different thicknesses measured by classical and nano photoelectron spectroscopies.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…At present, there exist several interpretations about the rotational disorder on this system. Several groups reported that the disorder is due to the rotation between graphene layers inside one single domain [14,15], the Bernal stacked azimuthally disordered graphene domains [12,[22][23][24], or a combination of AB stacked and twisted multilayers [26]. We now present our results obtained from graphene with different thicknesses measured by classical and nano photoelectron spectroscopies.…”
Section: Resultsmentioning
confidence: 84%
“…Based on theoretical calculations, renormalization of the Fermi velocity near the Dirac point is expected for very small twist angles [20,21]. On the other hand, Johansson and co-workers [12,22,23] have conducted μ-LEED and x-ray photoemission electron microscopy (XPEEM) studies that enabled them to measure single graphene domains on the C-face. The results showed the coexistence of micrometersized domains of single and multilayer graphene with different azimuthal orientations and no twisted layers within the grains.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining C forms a graphene film on the surface. However, the surface reconstructions and growth kinetics for each polar surface are different, resulting in different graphene growth rates, growth morphologies and electronic properties [30,[73][74][75]. Yakimova et al have analyzed the conditions for large-area graphene formation on SiC substrate [21].…”
Section: Graphitization Process Of Sic Polytypesmentioning
confidence: 99%
“…Graphene is atomic layer of sp 2 -hybridized carbon atoms covalently bonded in a honeycomb lattice via three in-plane σ-bonds and a remaining dangling π-bond EG grown on semi-insulating silicon carbide (SiC) substrates has a high potential for integration in the existing planar electronic devices technologies. While growth of graphene on the C-face (0001) of SiC substrates is difficult to control, the Si-face (0001) provides high quality, homogenous monolayer (ML) and bilayer (BL) graphene at a wafer scale, due to a self-consistent nature of the growth process [3][4][5]. Prototype devices based on EG have been demonstrated [6][7][8][9].…”
Section: Epitaxial Graphenementioning
confidence: 99%